2015
DOI: 10.1186/s12883-015-0514-y
|View full text |Cite
|
Sign up to set email alerts
|

Using network dynamic fMRI for detection of epileptogenic foci

Abstract: BackgroundEpilepsy is one of the most prevalent neurological disorders. It remains medically intractable for about one-third of patients with focal epilepsy, for whom precise localization of the epileptogenic zone responsible for seizure initiation may be critical for successful surgery. Existing fMRI literature points to widespread network disturbances in functional connectivity. Per previous scalp and intracranial EEG studies and consistent with excessive local synchronization during interictal discharges, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 69 publications
(79 reference statements)
1
15
0
Order By: Relevance
“…Hall and colleagues (17) reported that when compared to cocaine users, methamphetamine users showed significantly more reductions in gray matter in the left superior temporal gyrus (L-STG), particularly Heschl's gyrus, a region that might be considered part of a network system that is correlated with contextual verbal memory. Functional and structural studies have reported negative associations between activation and volume in the L-STG and performance on Logical Memory (137,138). Additionally, reduced cerebral perfusion in areas adjacent to the L-STG has been positively correlated with performance on the Babcock Story Memory Test (139).…”
Section: Discussionmentioning
confidence: 99%
“…Hall and colleagues (17) reported that when compared to cocaine users, methamphetamine users showed significantly more reductions in gray matter in the left superior temporal gyrus (L-STG), particularly Heschl's gyrus, a region that might be considered part of a network system that is correlated with contextual verbal memory. Functional and structural studies have reported negative associations between activation and volume in the L-STG and performance on Logical Memory (137,138). Additionally, reduced cerebral perfusion in areas adjacent to the L-STG has been positively correlated with performance on the Babcock Story Memory Test (139).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the fMRI signals overall are more random in these regions. Considering the equivalence between auto-correlation and PSSI measures ( He, B.J., 2014 , Nedic, S., et al, 2015 ), the reduction in PSSI indicates weaker autocorrelation/persistence in these regions. In line with previous reports of PSSI deviations from the neurotypical range in other neurological and psychiatric disorders ( Lai, M.C., et al, 2010 , Maxim, V., et al, 2005 , Mujica-Parodi, L.R., et al, 2014 , Nedic, S., et al, 2015 , Radulescu, A.R., et al, 2012 , Tolkunov, D., et al, 2010 ), the current study is the first to report reduced PSSI in cocaine addicts and its association with deficits in cognitive control.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, male adults with an autism spectrum condition showed a significant shift to randomness in endogenous brain oscillations, as compared to neurotypical individuals, in brain regions implicated in autism ( Lai et al, 2010 ). Our previous studies of power spectrum scale invariance (PSSI) as a measure of nonlinear complexity demonstrated that as the neural circuits become increasingly dysregulated, signal complexity of affected nodes deviates from an equilibrium value, as observed in trait anxiety, epilepsy and schizophrenia ( Mujica-Parodi, L.R., et al, 2014 , Nedic, S., et al, 2015 , Radulescu, A.R., et al, 2012 , Tolkunov, D., et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in epilepsy, seizure foci are shifted towards β = 1, as dense arrays of short-range connections (which may reflect compensatory sprouting in response to neuronal damage) locally constrain dynamics (Nedic et al, 2015). Figure 1 provides another example in which the particular type of dysregulation (Type 1 diabetes), in this case caused by weak inhibition, produces time-courses that are too stiff rather than too chaotic.…”
mentioning
confidence: 99%